Identification Of The Procoagulant Species In Ellagic Acid Solutions - Bock, Paul E; Shore, Joseph D (Thrombosis and Haemostasis, 1981)
The species of ellagic acid responsible for initiating intrinsic blood coagulation has been characterized. Ellagic acid is soluble ata level of 30 ± 10 μM in pH 7.4 Tris-saline buffer at 22°C. Dilution of soluble ellagic acid resulted in enhanced plasma procoagulant and kallikrein generating activity, and the appearance of a new absorbance spectrum. These effects were prevented by 1 mi4 EDTA, and the new species could be removed by centrifugation. Addition of stoichiometric Cu2+ to Millipore-filtered soluble ellagic acid generated an absorbance spectrum similar to that caused by dilution in the absence of EDTA, as well as procoagulant and kallikrein activities. Zn2+ and Co2+ caused similar spectral changes and prekail ikrein activation. Although no turbidity was visible and the spectral properties did not indicate extensive light scattering, centrifugation resulted in loss of the absorbance spectrum and activity. We conclude that the procoagulant activity of ellagic acid solutions can be ascribed to slowly settling insoluble aggregates of ellagic acid-metal ion complexes, which are formed with adventitious metal ions present in the diluting buffer. Formation of these aggregates could be prevented but not reversed by 1 mM EDTA. Although soluble ellagic acid may bind to Factor XII, it does not initiate blood coagulation or prekallikrein activation, since these activities were only associated with the insoluble species.